Partial differential equations for scientists and engineers - Farlow, Stanley J., 1937- (Dover Publications, 1993)
This highly useful text for students and professionals working in the applied sciences shows how to formulate and solve partial differential equations. Realistic, practical coverage of diffusion-type problems, hyperbolic-type problems, elliptic-type problems and numerical and approximate methods. Suggestions for further reading. Solution guide available upon request. 1982 edition.
Originally published: New York : Wiley, c1982.
Keywords: Differential equations, Partial.; elektronické knihy; electronic books